Computer simulation of binding free energy differences for the oppa:kxk system using the kbff20 force field - Ekama, Trust Onoriode (Kansas State University, 2023)
Free energy calculations are an important part of modern-day drug design processes and molecular dynamics (MD) simulation has become a crucial tool in predicting binding affinities of ligands to their substrates. The quality of a MD simulation depends on the degree of sampling of important events during the simulation, and the accuracy of the force field adopted to describe the interactions between the atoms and molecules included in the system of study. The KBFF20 force field is a recently developed protein force field that continues to be validated. Here we investigate its capabilities to represent solute-solute interactions in protein-ligand systems by calculating relative binding free energies for the OppA:KXK system and comparing the results with experimental data. OppA is a water-mediated oligopeptide binding protein with the remarkable characteristic of binding to 2-5 residue long peptides with little regard for their composition (amino acid sequence). Experimental binding free energies, enthalpies and entropies are available for the three residue peptides, KXK, where X is all twenty of the naturally occurring amino acid residues. Furthermore, X-ray crystal structures indicate that all twenty peptides bind to OppA with an identical pose. Here, we determine changes in free energy of binding of several KXK peptides to OppA using the KBFF20 force field. In particular, we address the issues of sampling, the presence of mobile water molecules in the binding site, and analytical corrections to the free energies for charged residues arising due to system size effects. Finally, we also investigate the role of bound ions close to the peptide binding site and their contribution to the free energy differences. In summary, the OppA:KXK system represents a unique system that is available to investigate the accuracy of peptide-protein interactions representative of all twenty amino acid side chains. However, significant care is required to obtain precise results using current computational approaches.
Keywords: Free energy calculations; OppA:KXK; KBFF20; Molecular dynamics; Computer simulation